Palavra e imagem: o livro ressignificado em Psiquê, de Ângela Lago - Camerlingo, Tamires Henrique Lacerda (2015)
This study aimed to analyze how a narrative can be built from the interaction between two languages: verbal and visual. The work Psiquê (2010) Angela Lake, was the object studied throughout this research. The author, rescuing the classical greek myth of Eros and Psyche, recounts the story of lovers with innovative features and instigators of the imagination. The author Teresa Colomer (2003), in The formation of the literary reader: children's storytelling and current youth has allowed us to understand a little more about the Lake trajectory within the historical context of children and youth literature in Brazil. The words deserve a single chapter, where you can discuss the importance of hybrid genre and its ability to unite prose and poetry without losing the quality of text, so we were guided by studies of Octavio Paz (2012), in The Bow and the lira. The author discusses the importance of word and its plural ability to be more than mere linguistic signs. The illustrations have preserved the poetic, as raised the multiplicity of meanings in this way were studied, first, alone. The light theories Sophie Van der Linden (2011) in Order to read the picture book could analyze the images so that each of them could exhibit its potency. But as word and image can not be dissociated from this context, we developed a final chapter to show the union between the two media. We note from the reflections of Mircea Eliade (2012), in Myth and reality that Psiquê extinguishes the boundaries of literary genres, recovering and returning the poetic origins